(untitled) (Materiali di Estetica. Terza serie, 2022)
Through the commentary on portraits (Lotto, Giorgione, Vermeer, L. Freud, Rembrandt, Tiziano, Bacon…), my contribution will develop two topics. In fact, the portrait calls to reflect both on the reversible dynamics of the gaze (between painter, subject and spectator, between presence and absence) and on the time of the individual as an experience and as a transformative process that tells a story.